2018
DOI: 10.1016/j.jid.2017.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-3 Loss Causes Leakage of Sweat from the Sweat Gland to Contribute to the Pathogenesis of Atopic Dermatitis

Abstract: The transfer of sweat to the skin surface without leakage is important for the homeostatic regulation of skin and is impaired in atopic dermatitis. Although the precise composition of the leakage barrier remains obscure, there is a large contribution from claudins, the major components of tight junctions. In humans, claudin-1, -3, and -15 are expressed on sweat ducts, and claudin-3 and -10 are expressed on secretory coils. Although only two claudins are expressed in murine sweat glands, we found that the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…On the ultrastructural level, the presence of barrier-forming TJs in sweat glands of human skin has already been shown in the 1970s and 1980s [ 104 , 105 , 106 ]. Sweat glands express occludin, claudin-1, claudin-3, claudin-4, claudin-10b and claudin-15 as well as ZO-1 and ZO-2 in human skin with varying expression patterns depending on the localization within the gland [ 107 , 108 , 109 ]. Claudin-1 is often absent from the barrier-forming TJs, while claudin-3, claudin-10 and claudin-15 seem to be more prominent.…”
Section: Which Skin Barriers Have To Be Overcome?mentioning
confidence: 99%
See 3 more Smart Citations
“…On the ultrastructural level, the presence of barrier-forming TJs in sweat glands of human skin has already been shown in the 1970s and 1980s [ 104 , 105 , 106 ]. Sweat glands express occludin, claudin-1, claudin-3, claudin-4, claudin-10b and claudin-15 as well as ZO-1 and ZO-2 in human skin with varying expression patterns depending on the localization within the gland [ 107 , 108 , 109 ]. Claudin-1 is often absent from the barrier-forming TJs, while claudin-3, claudin-10 and claudin-15 seem to be more prominent.…”
Section: Which Skin Barriers Have To Be Overcome?mentioning
confidence: 99%
“…Claudin-1 is often absent from the barrier-forming TJs, while claudin-3, claudin-10 and claudin-15 seem to be more prominent. Of note, in mouse skin, only claudin-3, claudin-4 and claudin-10 are present [ 109 ].…”
Section: Which Skin Barriers Have To Be Overcome?mentioning
confidence: 99%
See 2 more Smart Citations
“…Because we have shown here that TJs also form a barrier in human HFs and therefore contribute to overall barrier function of the skin we wanted to check whether Cldn-1 is also affected in HFs of lesional or non-lesional skin from AD patients compared to healthy control skin. In addition, it was recently shown that Cldn-1 is also down-regulated in sweat glands of lesional AD skin 38 .…”
Section: Resultsmentioning
confidence: 98%